IMPLEMENTASI LESSON STUDY DI KELAS IX D PADA MATERI KELISTRIKAN DAN TEKNOLOGI LISTRIK DI LINGKUNGAN UNTUK MENINGKATKAN KEMAMPUAN MINAT DAN HASIL BELAJAR KOGNITIF SISWA SMP NEGERI 2 TARAKAN - Dewi Kunarti (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2019)
Abstract: Lesson Study is an effort to improve the learning process and outcomes which is carried out collaboratively and continuously by a group of teachers. One aspect of improving the learning process using the Lesson Study-based CAR approach is the aspect of interest in learning. With the increasing interest in learning possessed by students, it will also have an effect on improving cognitive learning outcomes, especially in this research in class IX D on Electricity and Electrical Technology in the Environment at SMP Negeri 2 Tarakan. The approach used in this research is to follow the research flow Plan, Do, See. Conducted in 3 stages for 4 cycles. The plot, which begins with the planning stage (plan), at this stage, activities to analyze the needs and problems faced in learning are carried out. Furthermore, the implementation stage (do) is carried out, in the second stage, there are two main activities: 1) learning activities carried out by one of the model teachers, and 2) observation or observation activities carried out by other members or the Lesson Study community. And in the last stage, the reflection (see) is carried out after the teacher has learned in the classroom. Based on the research results obtained posttest. In the cognitive learning outcomes the average value in cycle I was 71.68, cycle II 76.06, cycle III 90.14, and cycle IV was 91.09. Furthermore, for the results of interest in learning, the average value in cycle I was 61.61, cycle II 61.94, cycle III 60.05, and cycle IV was 61.75. From the results of these studies, it can be concluded that the implementation of lesson study can increase interest and cognitive learning outcomes of class IX D students of SMP Negeri 2 Tarakan on electricity and electrical technology. Keywords: lesson study, interest, cognitive